Using positive behavioural support (PBS) for STOMP medication challenge. Issue 3 (3rd June 2019) - Gerrard, David; Rhodes, Jennifer; Lee, Ruth; Ling, Jonathan
Abstract : Purpose: The purpose of this paper is to investigate if positive behavioural support (PBS) can be an effective alternative to medication, and can aid medication reduction in people with a learning disability, autism or both who are prescribed psychotropic medication for behaviour thought to be challenging. STOMP is an initiative supported by NHS England which aims to reduce inappropriate prescribing of psychotropic medication, i.e. antipsychotics used for challenging behaviour in the absence of a documented mental health diagnosis. PBS has been described as the first line of intervention for behaviours which challenge, (NICE, 2015) and has been highlighted as a non-pharmacological alternative to, medication. Design/methodology/approach: A two-group, experimental design was utilised. Both groups were considered for medication reduction. The experimental group of 25 people received input from a specialist PBS team, while the control group of 29 people underwent unsupported medication challenge. Findings: There was a significantly higher success rate for medication reduction and discontinuation when PBS assessment and intervention was provided as an alternative to medication. Practical implications: This study indicates that providing PBS is associated with decreased medication and if replicated should be become standard practice for specialist teams. Originality/value: This is the first study to investigate the effect of PBS on medication reduction in patients prescribed psychotropic medication for behaviour thought to be challenging.